1992
DOI: 10.1246/cl.1992.1801
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Diastereofacial Selectivity in the Michael Addition Reactions of Lithiated 2-Aminoacetates and -acetamides to α,β-Unsaturated Carbonyl Compounds

Abstract: Unusual diastereofacial selectivities are observed in the Michael addition reactions of lithiated aminoacetates and -acetamides to α,β-unsaturated carbonyl acceptors. Lithiated (methylamino)acetates and -acetamides show opposite anti- and syn-selectivities, respectively, while lithiated (dialkylamino)acetates and -acetamides are both highly syn-selective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thus, the enolates of several differently protected glycinates 128 were added to a number of alkyl (2E)-4-bromobut-2-enoates 129 to yield, after trans-selective cyclizations, the correspondingly protected trans-(2-carboxycyclopropyl)glycine derivatives 130, several of which could be fully deprotected to trans-127 (Scheme 17, eq 2). [81][82][83][84][85] In a variant of this MIRC-type reaction, tert-butyl Ntrifluoroacetylglycinate (131) was deprotonated with lithium bis(trimethylsilyl)amide in the presence of zinc chloride, whereupon the chelated zinc (Z)-glycinate enolate 132 was formed. Subsequent trapping of the latter with methyl (Z)-4-(diethoxyphosphonyl)but-2-enoate as an electrophile af- 18).…”
Section: 4-methanoprolinementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the enolates of several differently protected glycinates 128 were added to a number of alkyl (2E)-4-bromobut-2-enoates 129 to yield, after trans-selective cyclizations, the correspondingly protected trans-(2-carboxycyclopropyl)glycine derivatives 130, several of which could be fully deprotected to trans-127 (Scheme 17, eq 2). [81][82][83][84][85] In a variant of this MIRC-type reaction, tert-butyl Ntrifluoroacetylglycinate (131) was deprotonated with lithium bis(trimethylsilyl)amide in the presence of zinc chloride, whereupon the chelated zinc (Z)-glycinate enolate 132 was formed. Subsequent trapping of the latter with methyl (Z)-4-(diethoxyphosphonyl)but-2-enoate as an electrophile af- 18).…”
Section: 4-methanoprolinementioning
confidence: 99%
“…A second trans -diastereoselective access to (2-carboxycyclopropyl)glycine 127 was realized by a so-called MIRC (Michael-induced ring closure) sequence. Thus, the enolates of several differently protected glycinates 128 were added to a number of alkyl (2 E )-4-bromobut-2-enoates 129 to yield, after trans -selective cyclizations, the correspondingly protected trans -(2-carboxycyclopropyl)glycine derivatives 130 , several of which could be fully deprotected to trans - 127 (Scheme , eq 2).
18 Synthesis of Racemic trans -(2-Carboxy- cyclopropyl)glycine via a Chelated Zinc Enolate of t -Butyl N -trifluoroacetylglycinate 86
…”
Section: 7 34-methanoglutamic Acid and Its Derivatives271 (2-carboxyc...mentioning
confidence: 99%
“…An interesting sequence giving rise to cyclohexyl amino acid derivatives was reported by Moreno-Manas et al, based on a double Michael addition and subsequent Dieckman condensation . But other nucleophiles such as the enolates of Schöllkopf's bislactim ethers, sarcosinates, or N , N -dibenzylglycinates also can be used.…”
mentioning
confidence: 99%
“…Besides the imines, the Schöllkopf bislactime ethers can be used for an asymmetric approach of that kind . Kanemasa et al used enolates of sarcosine esters and amides and observed selective anti or syn product formation, depending on the protecting groups used . An efficient synthesis of the syn product was also described by using enolates of N , N -dibenzylglycinate .…”
mentioning
confidence: 99%